Triple jump
During the World Championships in Athletics in August 1995 in Gothenburg Sweden, a research group had access to videotape the final of the mens triple jump. In this competition Jonathan Edwards broke the existing world record twice. The research group consisted of Per Aagaard, Morten Havkrog, Erik B. Simonsen, Gideon Ariel and Leif Dahlberg. The hop, step and jump were recorded by separate cameras with a shutter of 1/1000 sec. Later the 9 best athletes of the final were analysed by the APAS system.